Pengaruh Harga, Gaya Hidup Dan Kualitas Produk Terhadap Keputusan Pembelian Kopi Janji Jiwa Di Bekasi - Nazifa Fitri; Hadita Hadita (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Facing very rapid business developments, many companies are implementing better strategies to meet consumer needs and also provide the best service. So this research wants to find out whether there is an influence of price, lifestyle and product quality on purchasing decisions for Janji Jiwa coffee in Bekasi. This research method uses a quantitative approach by distributing questionnaires. The data was processed using SPSS by conducting Validity, Reliability, Determination Coefficient, Partial T Test and Simultaneous F Test. The results of this research show that the Lifestyle variable has a partial influence on the decision to purchase Janji Jiwa coffee in Bekasi, while the price and product quality variables have no partial and significant influence on the decision to purchase Janji Jiwa coffee in Bekasi. And the variables Price, Lifestyle and Product Quality together simultaneously influence the Purchase Decision for Janji Jiwa Coffee in Bekasi.